2018
DOI: 10.1038/s41598-018-19242-z
|View full text |Cite
|
Sign up to set email alerts
|

Three Dimensional Evaluation of Posterior Pole and Optic Nerve Head in Tilted Disc

Abstract: For over a century, tilted disc syndrome (TDS) has been defined vaguely. The lack of consensus of the terminology arises from the lack of understanding of the pathogenesis of this condition. Also, myopic discs with temporal crescents or peripapillary atrophy (PPA) are histologically indistinguishable from TDS. Therefore, we examined the morphological background of the extreme ONH appearances such as the myopic tilted disc and the TDS by analyzing the posterior segment of the eye from a three-dimensional (3D) p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…This study is a follow-up to our research on the posterior sclera biometrics of glaucoma using the novel parameter deepest point of eye (DPE). 12 , 17 We have suggested that glaucomatous eyes had the DPE situated deeply posterior to the optic disc, which was consistent with the comparison between the glaucomatous and nonglaucomatous eyes, and also with the progressive and nonprogressive glaucomatous eyes. 11 , 18 Moreover, it is well documented that peripapillary and ONH structures change over time in childhood.…”
supporting
confidence: 84%
“…This study is a follow-up to our research on the posterior sclera biometrics of glaucoma using the novel parameter deepest point of eye (DPE). 12 , 17 We have suggested that glaucomatous eyes had the DPE situated deeply posterior to the optic disc, which was consistent with the comparison between the glaucomatous and nonglaucomatous eyes, and also with the progressive and nonprogressive glaucomatous eyes. 11 , 18 Moreover, it is well documented that peripapillary and ONH structures change over time in childhood.…”
supporting
confidence: 84%
“…In the eyes in which the head of the optic nerve is deformed and therefore difficult to evaluate, we may assume that the macular region is less distorted, but this is not always true. The studies by Kim et al [ 34 , 35 ] have suggested that the outline of the entire posterior pole determines the possible configuration of the optic nerve head. So, the presence of irregularities in macular region could invalidate the evaluation of GCC in myopia.…”
Section: Discussionmentioning
confidence: 99%
“…In the eyes in which the head of the optic nerve is deformed and therefore difficult to evaluate, we may assume that the macular region is less distorted, but this is not always true. The studies by Kim et al (32,33) have suggested that the outline of the entire posterior pole determines the possible configuration of the optic nerve head. So, the presence of irregularities in macular region could invalidate the evaluation of GCC in myopia.…”
Section: Discussionmentioning
confidence: 99%